2018
DOI: 10.1002/ieam.4102
|View full text |Cite
|
Sign up to set email alerts
|

Practical advice for selecting or determining trophic magnification factors for application under the European Union Water Framework Directive

Abstract: European Union Directive 2013/39/EU, which amended and updated the Water Framework Directive (WFD; 2000/60/EC) and its daughter directive (2008/105/EC), sets Environmental Quality Standards for biota (EQS biota ) for a number of bioaccumulative chemicals. These chemicals pose a threat to both aquatic wildlife and human health via the consumption of contaminated prey or the intake of contaminated food originating from the aquatic environment. EU member states will need to establish programs to monitor the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 63 publications
(101 reference statements)
4
64
0
Order By: Relevance
“…Ci designates the predicted whole-body concentration in fish (Cifish) or the measured concentration in gammarids (Cigam). Note that this equation is consistent with the generic trophic magnification model, which for hydrophobic substances is based on concentrations in lipids (Burkhard et al 2013;Kidd et al 2019).…”
Section: Equationsupporting
confidence: 78%
See 2 more Smart Citations
“…Ci designates the predicted whole-body concentration in fish (Cifish) or the measured concentration in gammarids (Cigam). Note that this equation is consistent with the generic trophic magnification model, which for hydrophobic substances is based on concentrations in lipids (Burkhard et al 2013;Kidd et al 2019).…”
Section: Equationsupporting
confidence: 78%
“…TMFs are obtained by regression between the chemical concentrations in organisms of a food-web and their respective TLs (Borgå et al 2012); in principle, all concentrations refer to whole-body. The TMFs used for the tests were borrowed from previous studies on French riverine sites (Simonnet-Laprade et al 2019a; Simonnet-Laprade et al 2019b); while they came from field studies in a context relevant to the purpose of the present study, they were comparable to the TMFs retrieved from a literature review and screened according to Kidd et al (2019). The TMFs determined in French rivers are compiled in Table S4, and TMFs from the literature survey are compiled in Figure S1 and Table S5 in SM.…”
Section: Tmf Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it is strongly recommended to use all the data for TMF calculation because the real food-web is intrinsically incorporated in the assessment. Kidd et al (2018) also suggested key principles for evaluation of TMF studies including a minimum food web TL difference of 2.0 and balance in the number of samples for low and high trophic level species. Using all the data in Table 2 of Xue et al (2019), TMF were calculated as shown in Table 2 below [with TMFs of Xue et al (2019) in the last column].…”
Section: Measurement Of Tmfsmentioning
confidence: 99%
“…Indeed, from a risk-assessment point of view, mercury requires an approach based on establishing its bioaccumulative potential in resident biota rather than the typical toxicity-based approach commonly used for other trace elements [9,10]. Data from low trophic levels (i.e., plankton and benthic invertebrates) are necessary to estimate the trophic magnification factors (TMF) for a given food web to fulfil e.g., European regulatory requirements for bioaccumulative chemicals [11]. In the case of small organisms such as freshwater benthic invertebrates, collecting an adequate amount of biomass of resident biota for measuring Hg accumulation can be quite a time-and resource-intensive exercise.…”
Section: Introductionmentioning
confidence: 99%